Internal migration and mental health of the second generation. The case of Turin in the age of the Italian economic miracle. (July 2018) - Cardano, Mario; Scarinzi, Cecilia; Costa, Giuseppe; d'Errico, Angelo
Abstract: Until the first half of the '50s, Italy was an underdeveloped and mainly agricultural country. From the second half of the '50s to the late '70s, Italy was the theatre of a massive economic and social transformation which placed the country among the most developed economies in Europe. During those years, more than four million poor peasants migrated from the most economically depressed areas of the South to the North-West of the country. Turin was one of the preferred destinations of this exodus. It was this huge army of low-cost workers which made the economic miracle possible. This exodus has many traits in common with the more recent international migration, and can – by analogy – give a sense of where the latter may lead. This study analyzes the impact of these experiences on the mental health of individuals whose childhood was spent in Turin during the economic miracle, focusing on the most severe mental distress: psychosis. The data used for this purpose combine the results of a qualitative secondary analysis and a large archive of data which derives from the Turin Longitudinal Study (TLS). The study's main finding is that the offspring of Southern migrants are at a higher relative risk of psychosis (RR 1.61), compared to the "natives". It seems that the offspring of migrants have paid the price of their parents' migration project with the impairment of their own mental health. Highlights: Parallelism amid recent international migration and past Italian internal migration. Psychosis excess risk for Southern immigrants' offspring compared to native RR 1, 61. Tracing of prejudice and discrimination processes through biographical narratives. Ethnic penalty in education attainments for both generation 2 and 1.5 Integration of quantitative and qualitative evidence.